PENERAPAN DATA WAREHOUSE UNTUK SISTEM INFORMASI TINGKAT KESEHATAN BANK PADA BANK ABC - Dadang Iskandar Mulyana (STIKOM CKI, 2017)
The development and growth of the Bank is currently one of the indicators of economic growth of a country, ABC Bank is written here is a bank with the name of a hidden bank but exist in Indonesia to keep confidential data that has been obtained in research, ABC bank is located in almost 58 Main Branch Offices and 438 Sub-Branch Offices throughout Indonesia to conduct activities such as collecting funds from the public in the form of deposits and deposits and distribution to the community in the form of credit, in fact there are many other activities undertaken by banks in producing bank products, between (gyro), foreign exchange , checks, credit cards, bank guarantees, bilyet giros, collections, bank records, safe deposit boxes (SDB), call centers, electronic banking, debit cards and ATM cards, and credit cards, banks can assess the health of their own banks using government methods newly issued in PBI number 13/1 / PBI / 2011 article 2, the bank is required to conduct a health assessment or bank using a risk approach (Risk Based on Bank Rating) either individually or consolidatively, therefore perceived and required an integrated database that meets the needs of the analysis using data warehouse to support the connection of bank information systems to Business Intelligent, to meet those needs above then in the design Database processing using Datawarehouse that is able to analyze all transactions into the dashboard and tabular graphics to facilitate and interesting in reporting, this research. done with the current system analysis stages, report analysis, data warehouse planning, data warehouse design, data warehouse verification.